Community-acquired Klebsiella pneumoniae bacteremia: Global differences in clinical patterns - DURMUŞOĞLU, LÜTFİYE (CENTER DISEASE CONTROL, 2002)
We initiated a worldwide collaborative study, including 455 episodes of bacteremia, to elucidate the clinical patterns of Klebsiella pneumoniae. Historically, community-acquired pneumonia has been consistently associated with K. pneumoniae. Only four cases of community-acquired bacteremic K. pneumoniae pneumonia were seen in the 2-year study period in the United States, Argentina, Europe, or Australia; none were in alcoholics. In contrast, 53 cases of bacteremic K. pneumoniae pneumonia were observed in South Africa and Taiwan, where an association with alcoholism persisted (p=0.007). Twenty-five cases of a distinctive syndrome consisting of K. pneumoniae bacteremia in conjunction with community-acquired liver abscess, meningitis, or endophthalmitis were observed. A distinctive form of K. pneumoniae infection, often causing liver abscess, was identified, almost exclusively in Taiwan.
Keywords: PYOGENIC LIVER-ABSCESS; INTENSIVE-CARE UNIT; METASTATIC ENDOPHTHALMITIS; HEPATIC-ABSCESS; ENDOGENOUS ENDOPHTHALMITIS; PROGNOSTIC FACTORS; DIABETIC-PATIENTS; ETIOLOGY; TAIWAN; COMPLICATION